The Association Between Mycobacteria-Specific Antigen-Induced Cytokines and Host Response to Latent Tuberculosis Infection Treatment in a Chinese Population - Cao, Xuefang; Xin, Henan; Zhang, Haoran; Liu, Jianmin; Pan, Shouguo; Du, Ying; Feng, Boxuan; Quan, Zhusheng; Guan, Ling; Shen, Fei; Liu, Zisen; Wang, Dakuan; et al. (Frontiers in Microbiology, 2021)
Objectives: Exploring biomarkers monitoring latent tuberculosis infection (LTBI) treatment effectiveness would benefit optimizing the therapeutic regimen. This study aims to identify potential mycobacteria-specific antigen-induced cytokines associated with host responses to preventive treatment. Methods: Based on a randomized controlled trial on LTBI treatment among individuals with chest radiography abnormalities suggestive of prior tuberculosis (TB), the dynamic changed cytokines levels in QuantiFERON-TB Gold In-Tube (QFT) supernatants were estimated during the treatment by bead-based multiplex assays and enzyme-linked immunosorbent assay. Results: Totally, 63 treated participants and 32 untreated controls were included in the study. The levels of 13 background-corrected mycobacteria-specific antigen-stimulated cytokines (Basic FGF, GRO-α, IL-1α, IL-1ra, IL-12 (p70), SCF, TRAIL, IL-8, IFN-α2, IL-5, IL-12 (p40), LIF and IL-17A) were found to be statistically different between before and after treatment in treated participants, while no statistically differences were observed in untreated controls. Among these 13 cytokines, the level of IL-8 was significantly lower in QFT reversed group than in non-reversed group (p=0.028) among treated participants, while such a difference was not found for untreated controls (p=0.292). Conclusions: Our results suggested that the lower level of mycobacteria-specific antigen-induced IL-8 might be associated with host positive response to LTBI treatment.